Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Influence of carbohydrate on the microparticulation process of whey proteins: structural modifications and indicators of the Maillard Reaction - Igor L. de Paula; Natalia C. Mesa; Alan F. Wolfschoon-Pombo; Uwe Schwarzenbolz; Thomas Henle; Ítalo T. Perrone; Luiz Fernando C. de Oliveira; Rodrigo Stephani (International Dairy Journal, 2026)

(Poly)phenol metabotypes and cardiometabolic health: a systematic review - Wafa Alotaibi; Daniel Perrone; Xiaohe Liu; Celeste Lugtmeijer; James Pham; Selena Wu; Sara Dorottya Biro; Shradha Gurung; Wendy L. Hall; Ana Rodriguez-Mateos (Critical Reviews in Food Science and Nutrition, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Harnessing H2O2-induced susceptibility in Galleria mellonella larvae: A robust model for exploring oxidative stress and biomarkers - L.M.M. Mattos; R.N. Silva; L.G. Santos; L. Giovanini; V.S. Cruz; N.M.B. Barreto; D. Perrone; A.L.S. Santos; M.D. Pereira (Environmental Toxicology and Pharmacology, 2025)

Effect of microbial fermentation on functional traits and volatiloma profile of pâté olive cake - Paola Foti; Cinzia L. Randazzo; Mariateresa Russo; Rosa Di Sanzo; Flora V. Romeo; Antonio Scilimati; Morena Miciaccia; Maria Grazia Perrone; Cinzia Caggia (Food Research International, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Flower and fruit structure of the endangered species Petagnaea gussonei (Sprengel) Rauschert (Saniculoideae, Apiaceae) and implications for its reproductive biology - O. De Castro; P. Colombo; L. Gianguzzi; R. Perrone (Plant Biosystems, 2015)

Determination of aerosol deliquescence and crystallization relative humidity for energy saving in free-cooled data centers - L. Ferrero; L. D’Angelo; G. Rovelli; G. Sangiorgi; M. G. Perrone; M. Moscatelli; M. Casati; V. Rozzoni; E. Bolzacchini (International Journal of Environmental Science and Technology, 2015)

Bridge-Enhanced ACL Repair: A Review of the Science and the Pathway Through FDA Investigational Device Approval - Benedikt L. Proffen; Gabriel S. Perrone; Gordon Roberts; Martha M. Murray (Annals of Biomedical Engineering, 2015)

Semivolatile PAH and n-alkane gas/particle partitioning using the dual model: up-to-date coefficients and comparison with experimental data - G. Sangiorgi; L. Ferrero; M. G. Perrone; E. Papa; E. Bolzacchini (Environmental Science and Pollution Research, 2014)

GIS and geomatics for disaster management and emergency relief: a proactive response to natural hazards - M. Giardino; L. Perotti; M. Lanfranco; G. Perrone (Applied Geomatics, 2012)

Fusapyrone and Deoxyfusapyrone from Fusarium semitectumi Production and Biological Activities - C. Altomare; G. Perrone; M. C. Zonno; L. Polonelli; A. Evidente (Cereal Research Communications, 1997)